An Integrated Evaluation System for Budget Forecasting and Operating Performance with a Classified Budgeting Bibliography - Ijiri, Y.; Kinard, J. C.; Putney, F. B. (Journal of Accounting Research, 1968)
Y. Ijiri, J. C. Kinard, F. B. Putney, An Integrated Evaluation System for Budget Forecasting and Operating Performance with a Classified Budgeting Bibliography, Journal of Accounting Research, Vol. 6, No. 1 (Spring, 1968), pp. 1-28